Mekabu fucoidan: structural complexity and defensive effects against avian influenza A viruses - Synytsya, Andriy; Bleha, Roman; Synytsya, Alla; Pohl, Radek; Hayashi, Kyoko; Yoshinaga, Keiko; Nakano, Takahisa; Hayashi, Toshimitsu (Carbohydrate polymers, 2014)
Fucoidan from the sporophyll (Mekabu) of brown seaweed Undaria pinnatifida (wakame) is interesting due to its various biological activities. Mekabu fucoidan (Mw ∼ 9 kDa) of this study (MF) was previously isolated and characterized by chemical and separation methods including GPC and methylation analysis (Lee, Hayashi, Hashimoto, Nakano, & Hayashi, 2004). It was found that this fucoidan composed of partially sulphated (DS ∼ 0.72) fucose and galactose at approximately equal amounts. Methylation analyses revealed complex structure of MF. However, it has been still unclear about the linkages between units and substitution patterns. To solve these structural tasks, spectroscopic methods (FTIR, FT Raman and NMR) were used in the analysis of native MF and its deesterified derivatives. According to obtained results, this polysaccharide was defined as O-acetylated sulphated fucogalactan. The defensive effects of MF were evaluated on mice infected with avian influenza A viruses (H5N3 and H7N2 subtypes); its efficacy was determined in reducing viral replication and increasing antibody production. Oral administration of MF resulted in suppressing virus yields. In addition, the production of neutralizing antibodies and mucosal IgA in the animals inoculated with the avian influenza A viruses was significantly increased. These results suggested that MF could be used for the prevention of viral infection.
Keywords: Animals; Antiviral Agents; kachny; Influenza A Virus, H7N2 Subtype; Female; Spectroscopic methods; antivirové látky; ženské pohlaví; Ducks; Adjuvants, Immunologic; Antibody Formation; polysacharidy; replikace viru; ptačí chřipka u ptáků; Mice; Immunostimulating effect; tvorba protilátek; Mice, Inbred BALB C; myši; virus chřipky A; Avian influenza A virus; Influenza A virus; mořské řasy; Mekabu fucoidan; myši inbrední BALB C; virus chřipky A, podtyp H7N2; Influenza in Birds; Undaria; Sporophyll Undaria pinnatifida; zvířata; Virus Replication; Seaweed; adjuvancia imunologická; Polysaccharides